ESSENTIALS AND FEATURES OF TRADITIONAL IRANIAN BAZAARS (COMPARISON OF HAMEDAN BAZAAR AND ISTANBUL GRAND BAZAAR) - Zahra Kiahchin Maryan , Mehrdad Karimi Moshaver (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Traditional Iranian bazaars have been the backbone of cities, though few literature has addressed their architecture and buildings. The Iranian bazaar has been well-known around the world for the features and the word bazaar has entered all languages ??of the world. As an advantage, this study reviewed the essentials and features of traditional Iranian markets. Looking at the architectural past of these spaces will help designers to help the originalism of new and modern buildings. Hamedan Bazaar has long been an economic, commercial and trade center since the city of Hamedan is situated on the western communication routes to the center of Iran. Hamedan Bazaar has played a significant role in the development and prosperity of the city. This paper inspected the architectural features of Hamedan and Istanbul bazaars and compared them. This was done in order to realize the salient and unique features of this architectural masterpiece and its significance all over the world. The data was collected through a descriptive-analytical approach, library and field research, frequent presence in the architectural place, photography and conversation with architects.